2015
DOI: 10.1007/s00256-015-2212-7
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral atypical femoral fractures: how much symmetry is there on imaging?

Abstract: Patients with unilateral atypical femoral fractures are likely to be diagnosed with a contralateral AFF within the first year of presentation. Bilateral AFFs commonly have similar imaging features, including location along the femur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…In this study, every case had multiple risk factors associated with medical conditions and medication history. However, there was no case that had curvature of the femoral diaphysis, as shown in Figures 1-4 [12]. In this study, the 3 Case Reports in Orthopedics patient described in Case 1 first experienced her right femoral "subtrochanteric" fracture and later the left femoral "diaphyseal" fracture; this seems a relatively rare case.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In this study, every case had multiple risk factors associated with medical conditions and medication history. However, there was no case that had curvature of the femoral diaphysis, as shown in Figures 1-4 [12]. In this study, the 3 Case Reports in Orthopedics patient described in Case 1 first experienced her right femoral "subtrochanteric" fracture and later the left femoral "diaphyseal" fracture; this seems a relatively rare case.…”
Section: Discussionmentioning
confidence: 57%
“…Probyn et al reported a strong correlation between bilateral AFF locations, with 58 of 76 (76.3%) occurring within <5 cm and 41 of 76 (53.9%) within ≤2.5 cm. They concluded that bilateral AFFs commonly have similar imaging features, including location along the femur [ 12 ]. In this study, the patient described in Case 1 first experienced her right femoral “subtrochanteric” fracture and later the left femoral “diaphyseal” fracture; this seems a relatively rare case.…”
Section: Discussionmentioning
confidence: 99%
“…5 The 25% reduction in com posite outcomes of serious neonatal morbidity is limited by the unclear effect on outcomes such as respiratory distress syndrome and intraven tricular hemorrhage. …”
Section: A Single Course Of "Rescue" Corticosteroids May Be Consideredmentioning
confidence: 99%
“…Meanwhile radiological analyses and pedagogical guides to the recognition of various features of AFFs have also been published [17,2429].…”
mentioning
confidence: 99%